Identifying and managing frailty in Brazil: a scoping review protocol - Melo, Ruth Caldeira de; Cervato, Carina Junqueira; Aprahamian, Ivan; Gavin, James; Robinson, Katie; Frost, Rachael; Azevedo, Paula Schmidt [UNESP]; Villas-Boas, Paulo [UNESP]; Hinsliff-Smith, Kathryn; Gordon, Adam L. (Wolters Kluwer, 2020)
OBJECTIVE: The objective of this review is to scope the evidence on how researchers, health, and social care professionals in Brazil currently identify and manage frailty in older adults. INTRODUCTION: The rapidly aging population and associated increased healthcare usage by older people with frailty are challenging the sustainability of healthcare for older people in Brazil. Understanding how frailty is identified, measured, categorized, and managed in Brazil is an important part of building a response to the challenge. INCLUSION CRITERIA: This scoping review will consider studies that included older Brazilian adults (≥60 years old) recruited from different settings (community, primary care, health care centers, hospital, and long-term care institutions). Studies will be included if they involved any kind of frailty assessment (tools, scales, and measures) and/or interventions. This review will consider all study designs, regardless of their rigor. National policies for older people will be also be considered for analysis. METHODS: Indexed and gray literature in English or Portuguese from 2001 to the present will be considered. The searches will be conducted using bibliographic databases, university repositories, and the Brazilian Government official database. The studies will be independently screened according to the inclusion criteria by two reviewers based on their title, abstract, and full text. In case of disagreement, a third reviewer will be consulted. A customized data extraction form will be used to extract data from the included studies. The results will be presented in tabular form, accompanied by a narrative summary related to the objective of the present scoping review.